Edging towards hedging - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
This time we re not talking about hedging risks, as we have of late, but of real, live, green hedges. They help to make a brown environment greener, and more pleasant for their shade, view, flowers and fruits, and they contribute to a healthy...